Early supported discharge for older adults admitted to hospital with medical complaints: a protocol for a systematic review - Susan Williams; Catherine Peters; Aoife Leahy; Elaine Shanahan; Fiona Steed; Ann-Marie Morrissey (BMJ Open, 2021)
Introduction Early supported discharge (ESD) aims to link acute and community care, allowing hospital inpatients to return home and continue to receive the necessary input from healthcare professionals that they would otherwise receive in hospital. The concept has been researched extensively in the stroke population, showing reduced length of stay for patients and improved functional outcomes. This systematic review aims to explore the totality of evidence for the use of ESD in an older adult population who have been hospitalised with medical complaints.Methods A systematic review of randomised controlled trials and quasi randomised controlled trials will be carried out in line with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Studies will be included if they provide an ESD intervention to older adults admitted to hospital for medical complaints compared with continuing inpatient care. MEDLINE, CINAHL, CENTRAL and EMBASE databases will be searched. The primary outcome measure will be length of hospital stay, secondary outcomes will include functional abilities, falls, quality of life, carer and patient satisfaction, unplanned emergency department re-presentation, unscheduled hospital readmission, nursing home admission or mortality. Titles and abstracts of studies will be screened independently by two authors. The Cochrane Risk of Bias Tool will be used independently by two reviewers to assess the methodological quality of the included studies. GRADE will be used to assess the quality of the body of evidence. A pooled meta-analysis will be conducted using RevMan software V.5.4.1, depending on the uniformity of the data.Ethics and dissemination The authors will present the findings of the review to a patient and public involvement stakeholder panel of older people that has been established at the Ageing Research Centre in the University of Limerick. Formal ethical approval is not required for the review as all data collected will be secondary data and will be analysed anonymously.PROSPERO registration number CRD42021223112.